FtsZ as a novel target for antibiotics development: Promises and challenges - Ming-Wei Wang; Kaini Hang; Wei Han; Xin Li; Qingtong Zhou; Dehua Yang (Acta Pharmaceutica Sinica B)
Filamenting temperature-sensitive mutant Z (FtsZ), a protein essential for bacterial cell division, is highly conserved across bacterial species but absent in humans, positioning it as a strategic target for the development of antibiotics. Significant efforts to identify FtsZ inhibitors—via biochemical assays (e.g., GTPase activity) and cellular approaches (e.g., immunofluorescence)—have yielded over 100 natural products and synthetic compounds, whose cheminformatics clustering underscores a limited chemical diversity among the current scaffolds. Structural studies, including X-ray crystallography and cryo-electron microscopy, have resolved 97 FtsZ structures revealing conserved polymerization mechanisms and conformational plasticity, as exemplified by extremophile adaptations (e.g., Shewanella benthica from the high-pressure environment of the Mariana Trench's Challenger Deep). However, clinical translation is hindered by weak binding affinities, inhibitory inefficacy, dynamic conformational flexibility, and evolving drug resistance linked to FtsZ's functional plasticity. To address these challenges, future efforts should be directed to resolve transient assembly intermediates, leveraging machine learning with high-throughput screening, and integrating structural biology with pharmacokinetic optimization. Multidisciplinary strategies combining these approaches hold promise for translating FtsZ-focused research into clinically viable therapies, addressing the critical unmet need posed by antibiotics resistance.